Manifestation of meaning in national identity through semiotic theory approach in the national day logo of Malaysia / Siti Fairuz Md Hashim - Md Hashim, Siti Fairuz (2023)
The lack of local research on the meaning of the National Day logo has resulted in people not understanding the meaning of the National Day logo. This has caused a lack of patriotism among the community. The spirit of nationalism must exist in the community by appreciating the true meaning of independence. The National Day logo is designed to give awareness to the people and is also one of the ways used by the government to convey its desire and mandate. The identity of a country will be reflected in the Malaysian National Day logo. So, this research aims to comprehensively analyze the meaning of each character found in the Malaysian National Day logo by using sign and symbol theory. After conducting a comprehensive study, the researcher used theories from the Charles Sanders Peirce theory of Semiotic [representational, object, and interpretation] and the basic theory of formalistic (element of art and principle of design) in analyzing this logo. The Malaysian National Day logo is analyzed based on several characteristics of the logo, namely color, typography, shape, and visuals. This research was conducted using qualitative research methods using documents, observation, and interviews. This method of combining three findings in the form of triangulation combines a descriptive approach to obtain accurate and comprehensive research data. Findings from this researcher found that some of the characteristics of the National Day logo are such as shape, color, typography, and visuals. There are four types of National Day logos, which are logotypes, symbolic logos, abstract logos, and combination logos. The national identity elements found in the Malaysian National Day Logo include the 1Malaysia icon, the Malaysian flag, hibiscus flowers, Vision 2020 musical instruments, and human figures. This research has provided a complete contribution to the interpretation and design evolution of the Malaysian National Day logo from 1976 until 2020. A type of national identity symbol that has been clarified can be used as a guideline for the Government and designers in designing the National Day logo in the future.